The Influence Of Home Environmental Factors On Patient Care With Chronic Obstructive Pulmonary Disease (COPD) - Adhyatma A; Yusraa, Yusraa; Sallo, Andi Kamal M.; Cahya, M. Robby Fajar; Idris, Baiq Nurainun Apriani; Rahmat, Rezqiqah Aulia (Sean Institute, 2024)
The influence of the home environment on the care of patients with chronic obstructive pulmonary disease (COPD) is an important factor in the management of this condition. The